2005
DOI: 10.1016/j.molbrainres.2005.02.012
|View full text |Cite
|
Sign up to set email alerts
|

From synapse to gene product: prolonged expression of c-fos induced by a single microinjection of carbachol in the pontomesencephalic tegmentum

Abstract: It is not known how the brain modifies its regulatory systems in response to the application of a drug, especially over the long term of weeks and months. We have developed a model system approach to this question by manipulating cholinergic cell groups of the laterodorsal and pedunculopontine tegmental (LDT/PPT) nuclei in the pontomesencephalic tegmentum (PMT), which are known to be actively involved in the timing and quantity of rapid eye movement (REM) sleep. In a freely moving feline model, a single microi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…However there are reports of delayed and/ or protracted Fos expression (Quattrochi, Bazalakova, & Hobson, 2005;Xu, Zheng, Ho, & Qian, 2006). It is noteworthy that the latter involve plasticity-related longterm changes in brain function, as is the case for the effects of ''neonatal handling.…”
Section: Discussionmentioning
confidence: 99%
“…However there are reports of delayed and/ or protracted Fos expression (Quattrochi, Bazalakova, & Hobson, 2005;Xu, Zheng, Ho, & Qian, 2006). It is noteworthy that the latter involve plasticity-related longterm changes in brain function, as is the case for the effects of ''neonatal handling.…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of these nuclei blocks these waves. [108][109][110] More extensive Fos mapping has been done to identify neurons activated during REM sleep in the rat. Verret et al 111 found that only a few cholinergic neurons from the laterodorsal and pedunculopontine tegmental nuclei were Fos-labeled after REM sleep.…”
Section: Neuronal Activity Transmitter Releasementioning
confidence: 99%
“…Because the formation of partner preferences in male prairie voles requires rather long sexual interactions with a female (up to 24 h, Insel et al, 1995, Winslow et al, 1993), and surprisingly prolonged Fos expression can be seen after acute or chronic social or other stimulation (Bullitt et al, 1992, Matsuda et al, 1996, Quattrochi et al, 2005, Ricci et al, 2007, Stack and Numan, 2000, Wrynn et al, 2000, Xu et al, 2006), we also examined Fos expression in TH-ir cells of the pBST and MeApd after males cohabitated with a sexually receptive female for 6 or 24 hr.…”
mentioning
confidence: 99%